The Promotion of Creativity of Vocational College Students: The Role of Parent-Child Relationship, Emotional Intelligence, and Grit - Wu, Yushen; Wu, Yubin; Chong, Daohan; Zhang, Wen (Frontiers in Psychology, 2021)
Abstract: Objective: To examine whether emotional intelligence played a mediation role in the association between parent-child relationship and vocational college student's creativity, and whether grit moderated this mediating process. Methods: 663 vocational college students participated in this study and completed four questionnaires at three time points, which included measures of parent-child relationship, creativity, emotional intelligence and grit. Results: (1) emotional intelligence mediated the relationship between parent-child relationship and vocational college student's creativity; (2) grit moderated the mediating role of emotional intelligence between parent-child relationship and vocational college student's creativity. Conclusion: parent-child relationship had both direct effects on vocational college student's creativity and indirect effects through emotional intelligence. Grit moderates the effect of emotional intelligence on vocational college student’s creativity.